Beyond the Office: Navigating Ergonomic Mismatch and Psychosocial Challenges in Long-Term Remote Work - Serpian, Serpian; Asmar, Kurniati; Hirman, Hirman; Rahmatillah, Rahmatillah; Abdul-Rahaman, Osman (Journal of Business Administration (JBA), 2026)
This study examines the in-depth experiences of long-term remote workers as they navigate physical and psychosocial challenges within their domestic environments. By integrating a Macroergonomics perspective and Interpretative Phenomenological Analysis (IPA), it addresses the gap in reductionist literature that separates physical pain from mental stress. We frame home ergonomics as a complex ecosystem involving space negotiation and "ergonomic improvisation." Methodologically, this qualitative study uses an IPA design with purposive sampling of knowledge-based workers who have: 1) at least two years of full remote experience, and 2) high work intensity on Visual Display Terminals (VDTs). Data from semi-structured interviews were analyzed using thematic analysis. The research identified four superordinate themes: 1) domestic workstation improvisation, where using multifunctional areas like sofas creates an ergonomic mismatch; 2) physiological impact, characterized by high rates of Musculoskeletal Disorders (MSDs) due to sedentary behavior; 3) psychosocial dynamics, where social isolation and telepressure erode mental well-being; and 4) blurring of work-life boundaries, where working in bedrooms or across asynchronous time zones disrupts recovery. It is concluded that conventional ergonomic interventions are inadequate. Instead, a holistic Macroergonomics approach is needed, integrating: 1) workflow redesign, 2) boundary management training, and 3) structured virtual social support to ensure the sustainability and well-being of remote workers.